2006
DOI: 10.1038/sj.onc.1209382
|View full text |Cite
|
Sign up to set email alerts
|

Achaete-scute like 2 (ascl2) is a target of Wnt signalling and is upregulated in intestinal neoplasia

Abstract: Achaete-scute like (ASCL)2 is a basic helix-loop-helix transcription factor essential for the maintenance of proliferating trophoblasts during placental development. Using oligonucleotide microarrays we identified ascl2 as a gene significantly upregulated in colorectal adenocarcinomas (n ¼ 36 cancers, n ¼ 16 normals; 15-fold, Po0.0001). This finding was confirmed by quantitative reverse transcriptase (RT)-PCR on large intestinal cancers (n ¼ 29 cancers, n ¼ 16 normals; 10-fold, Po0.0001).In situ hybridization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
113
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(118 citation statements)
references
References 22 publications
4
113
1
Order By: Relevance
“…Immunohistochemistry for h-catenin was done on tumor xenograft tissue, skin and intestine harvested at the termination of efficacy studies. Tissues were formalin-fixed, paraffin-embedded, and serial sections were subjected to antigen retrieval (Dako Target Retrieval), following which h-catenin was detected with a monoclonal antibody (clone 14; BD PharMingen) as previously described (33). The sections were counterstained with hematoxylin (Vector Lab) and mounted using Histomount (Zymed).…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemistry for h-catenin was done on tumor xenograft tissue, skin and intestine harvested at the termination of efficacy studies. Tissues were formalin-fixed, paraffin-embedded, and serial sections were subjected to antigen retrieval (Dako Target Retrieval), following which h-catenin was detected with a monoclonal antibody (clone 14; BD PharMingen) as previously described (33). The sections were counterstained with hematoxylin (Vector Lab) and mounted using Histomount (Zymed).…”
Section: Methodsmentioning
confidence: 99%
“…2C). Since Lgr5 and Ascl2 have been found to be Wnt target genes [25,26], it may be argued that their reduced expression levels upon Brg1 loss are merely a result of attenuated Wnt signaling rather than an indicator of stem cell depletion. In order to overcome this limitation, we examined expression levels of Olfm4, a Wntindependent stem cell marker [27].…”
Section: Brg1 Loss Compromises Stem Cell Maintenance In the Murine Smmentioning
confidence: 99%
“…Of the genes downregulated, Ascl2 was reduced back to wild-type levels. Recent studies have shown that Ascl2 is a Wnt target gene and overexpression of this alone is sufficient to cause increased intestinal enterocyte proliferation and crypt size (Jubb et al, 2006;van der Flier et al, 2009). This reduction of Ascl2, in conjunction with reduction of Cyclin D2, provides a ready mechanism for reduced crypt proliferation and size in c-Myc heterozygotes.…”
mentioning
confidence: 99%